Assessing and Treating Trauma in Detained Adolescents: A Pre–Post Within Subjects Evaluation - Calleja, Nancy G. (Journal of child and family studies, 2020)
Objectives This investigation evaluated trauma-focused cognitive behavioral therapy (T-F CBT) with detained male adolescents with serious offending behaviors. Methods One hundred and seventeen youth with trauma symptoms participated in an average of twelve T-F CBT individual sessions. Trauma symptoms were assessed prior to and following treatment using the Trauma Symptom Checklist for Children (TSCC) and a paired sample t -test was used to analyze changes from pre- to posttest. Results Trauma symptoms in five of the six scales (i.e., anger, depression, anxiety, posttraumatic stress, dissociation) were significantly reduced following treatment. Conclusions T-F CBT may be effective in reducing general trauma symptoms among detained adolescents; assessing and treating trauma symptoms are recommended as standard protocol in the juvenile justice system; and T-F CBT may be effective without caregiver participation.